Analysis of significantly associated regions and candidate genes for dwarf stem trait in Brassica napus based on BSA-sequencing - ZHAO Weiguo; TA Na; WANG Hao; YANG Zelin (Xibei zhiwu xuebao)
[Objective] The study aims to reveal the genetic loci and candidate genes associated with the dwarf trait in Brassica napus, laying a foundation for the improvement of plant height and the breeding of lodging resistant B. napus varieties. [Methods] Rapeseed dwarf stem DW1 was used to cross with tall stem lines WH14 and WH20, respectively, and the F1 and F2 generations were used to analyze the genetic mechanism behind the dwarf trait. Meanwhile, two mixed DNA pools, one from extremely tall and the other from dwarf stem lines, constructed from F2 segregated population of dwarf stem DW1 and tall stem WH20 hybrid combination, were sequenced and analyzed base on BSA-seq technology, and the significant association regions and candidate genes associated with dwarf trait were identified. [Results] (1) The dwarf trait of B. napus DW1 was a quality trait and was controlled by one pair of incomplete dominant genes. (2) Twenty-two genomic regions significantly associated with dwarf trait were identified within the 21.78-23.88 Mb region on chromosome A06, with the maximum interval of 46.71 kb and the minimum interval of 0.64 kb. (3) Potential candidate genes, including BnaA06g27050D, BnaA06g34100D, BnaA06g34810D, BnaA06g35080D , and BnaA06g36480D , were identified in significantly associated regions on chromosome A06, which were related to the regulation of auxin and gibberellin signal transduction, respectively. [Conclusion] The dwarf trait herein is a quality trait controlled by one pair of incomplete genes. One significantly associated region was identified in the region from 21.78-23.88 Mb on chromosome A06. Five candidate genes within the significantly associated regions were identified and involved in the regulation of plant auxin synthesis and gibberellin signal transduction.